1998
DOI: 10.1300/j031v10n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Area Agency on Aging Outreach and Assistance for Households with Older Carers of an Adult with a Developmental Disability

Abstract: A demonstration project was undertaken in the state of New York to assess how area agencies on aging (AAAs) would approach outreach and direct aid to families caring for someone with a developmental disability. It was found that AAAs organized their outreach and direct-aid efforts using three main approaches: direct operation, contract operations, and multi-organizational. They generally organized staff time so that about two days per week of effort was devoted to undertaking outreach activities, conducting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…These family caregivers have traditionally provided lifelong caregiving for the person with intellectual disability; nonetheless, they are often ignored by the formal service systems and are highly likely to be out of touch with the formal support services that are available (Bigby & Ozanne, 2004;Haveman, Berkum, Reijnders, & Heller, 1997;Janicki, McCallion, Force, Bishop, & Lepore, 1998;Walker & Walker, 1998). Hong et al's (2001) study compared aging mothers over and below 65 years old and found that younger mothers were more likely to have a larger social support network and to receive more emotional support.…”
mentioning
confidence: 99%
“…These family caregivers have traditionally provided lifelong caregiving for the person with intellectual disability; nonetheless, they are often ignored by the formal service systems and are highly likely to be out of touch with the formal support services that are available (Bigby & Ozanne, 2004;Haveman, Berkum, Reijnders, & Heller, 1997;Janicki, McCallion, Force, Bishop, & Lepore, 1998;Walker & Walker, 1998). Hong et al's (2001) study compared aging mothers over and below 65 years old and found that younger mothers were more likely to have a larger social support network and to receive more emotional support.…”
mentioning
confidence: 99%
“…Examples of bridging tasks that were being discussed currently in practice were mandated joint planning initiatives between sectors [24], specific personnel such as registered nurses in ID who have the capacity to bridge aging and ID [36], and funding for cross-disability research and training centers on aging with a disability [64]. Bridging tasks reviewed in original research studies included pilot projects involving joint programming between disability services client and aged care residents [34,47], a palliative care educational program for staff caring for those with Intellectual Disabilities [37], and area agencies incorporating linkages with Developmental Disability agencies [46]. Examples of bridging tasks that were being called for were policy development and funding mechanisms covering aging and disability housing services, to enable aging in place for those with I/DD [26], training across staff regarding physical, cognitive and social changes in older adults with disabilities [8,39] and collecting data from individuals aging with disability to determine unmet needs and identify best practices [7].…”
Section: Perspectives Of Bridging Tasks Discussedmentioning
confidence: 99%
“…The primary stakeholder group discussed was the Administration for Community Living in the United States, responsible for interpreting and developing policies pertaining to services for older adults and individuals with disability [55,57]. The legislation most frequently discussed to facilitate bridging was the Older Americans Act in the United States and specifically the different amendments to the act at the end of the twentieth century, which authorized state funding for older adults with disability services, and required greater collaboration between agencies serving older adults and those supporting individuals with disability [46]. No studies evaluated outcomes of the bridging activities in the policy domain, however, policy implementation was noted to drive other bridging tasks in the health care and social services domain including, collaboration and planning across aging and disability services to support service development with the goal of enabling older adults and those with disabilities to fully participate in their communities [24].…”
Section: Bridging Tasks Organized Temporally and By Level Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests that older families are reluctant to plan for the future, resulting in a crisis-oriented move for the relative with an ID, financial woes, and unexpected dilemmas for siblings or extended family (Heller, 2001). They may also be unknown to ID services (Janicki, McCallion, Force, Bishop, & LePore, 1998) and may come forward only in times of desperate need. To address these issues, models of futures or permanency planning have evolved.…”
Section: Practice and Concerns With Older Familiesmentioning
confidence: 99%